Cooperative sensing in cognitive radio networks-avoid non-perfect reporting channel - Abdelhameed Mokhtar, Rania; Khatun, Sabira; Mohd Ali, Borhanuddin; Ramli, Abdul Rahman (Science Publications, 2009)
Problem statement: Cognitive radio is a candidate technology for more efficient spectrum utilization systems based on opportunistic spectrum sharing. However, a common assumption regarding cognitive radios is that they are unlicensed spectrum users that should defer to (avoid interfering with) existing primary sources. Therefore effective sensing of primary users was a major focus of current research. Cooperative spectrum sensing had been proposed to overcome the problem associated with the local sensing node problem-due to noise uncertainty, fading and shadowing. However, reporting the sensing result required perfect channel to avoid degradation in sensing performance due to fading. It also required a large bandwidth assuming large number of cognitive user. Approach: In this study we presented a hard decision auto-correction reporting scheme that directly corrects the errors in the reported bit and further minimizes the average number of reporting bits by allowing only the user with a detection information to report its result. We used analytical formulation to investigate the reporting scheme, by employing such selection technique; the reporting error due to the fading channel was reduced. Results: The sensing performance was investigated and we showed through simulations and probabilistic analysis the sensing performance improvements achieved via the proposed method. Numerical result showed much decrease in reporting bit without affecting the sensing performance.